PELAKSANAAN KEWENANGAN PENAHANAN TERHADAP DEBITOR PAILIT MENURUT UU RI NO 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU - Jimmy Simanjuntak (to-ra, 2017)
Abstract The Indonesian Criminal Code Procedure (KUHAP) provides fundamental legal basis in conducting detention, in concern that the suspect/defendant shall conduct escapement, erasure or destruction of the evidence, or shall conduct recidivism. Law Number 37 of 2004 regarding Bankruptcy and Suspension of Debt Payment Obligation also regulates regarding Detentions towards Bankrupt Debtors on the obligations as Bankrupt Debtors in providing important information/details towards the Administrators, Supervisory Judge, or the Administrators Members concerning the Debtors assets which then shall be managed and settled as bankruptcy assets; however this does not cover the mechanism for detention undertook by the Public Prosecutor evidently appointed by the Supervisory Judge. Keyword: kewenangan penahanan terhadap debitor pailit